Upper Normal Limit of Thyroid-Stimulating Hormone and Metabolic Syndrome in Iranian Patients with Obesity - Zohreh Nozarian; Alireza Abdollahi; Vahid Mehrtash; Hirbod Nasiri Bonaki (Iranian Society of Pathology, 2017)
Background:The current study aimed at evaluating the association between thyroid-stimulating hormone (TSH) level in upper normal limits with metabolic syndrome, modifiable risk factor for cardiovascular disease, and its components according to Adult Treatment Panel III of National Cholesterol Education Program. Methods: The current cross sectional study recruited 82 patients with euthyroid overweight or obesity. They all had body mass index (BMI) higher than 25 kg/m2. The patients were categorized in 2 groups: Group 1 (patients with metabolic syndrome) and Group 2 (patients with non-metabolic syndrome). Demographic features and anthropometric indices were all appraised by a trained examiner. Metabolic syndrome components, BMI, age, gender, C-reactive protein (CRP), and thyroid function test (TFT) were assessed and compared. Results: Age, triglyceride level, waist circumference, hypertension frequency, BMI and CRP were significantly higher in group 1. The most prevalent metabolic syndrome criterion was low level of serum high density lipoprotein (HDL). Patients with metabolic syndrome had greater TSH level, but it was not statistically significant (P-value=0.636). Euthyroid patients with TSH levels in the range of 3.88-5 mIU/L had 5.89 (95% confidence interval (CI) = 1.02 to 17.64) times higher risk of developing metabolic syndrome than other TSH values. After age adjustment, the relationship between the upper quartile of TSH level and the metabolic syndrome became insignificant (OR=2.97, 95% CI=0.51 to 17.2). Conclusion: TSH in upper normal limits was statistically correlated with metabolic syndrome. However, after adjustment for age, it became insignificant. Relationship between thyroid hormones and metabolic syndrome may be confounded by other important cardiovascular risk factors in euthyroid patients.